BMPQ-1 binds selectively to (3+1) hybrid topologies in human telomeric G-quadruplex multimers. Issue 20 (20th October 2020) - Gao, Chao; Liu, Zhu; Hou, Haitao; Ding, Jieqin; Chen, Xin; Xie, Congbao; Song, Zibing; Hu, Zhe; Feng, Mingqian; Mohamed, Hany I; Xu, Shengzhen; Parkinson, Gary N; et al.
Abstract: A single G-quadruplex forming sequence from the human telomere can adopt six distinct topologies that are inter-convertible under physiological conditions. This presents challenges to design ligands that show selectivity and specificity towards a particular conformation. Additional complexity is introduced in differentiating multimeric G-quadruplexes over monomeric species, which would be able to form in the single-stranded 3′ ends of telomeres. A few ligands have been reported that bind to dimeric quadruplexes, but their preclinical pharmacological evaluation is limited. Using multidisciplinary approaches, we identified a novel quinoline core ligand, BMPQ-1, which bound to human telomeric G-quadruplex multimers over monomeric G-quadruplexes with high selectivity, and induced the formation of G-quadruplex DNA along with the related DNA damage response at the telomere. BMPQ-1 reduced tumor cell proliferation with an IC50 of ∼1.0 μM and decreased tumor growth rate in mouse by half. Biophysical analysis using smFRET identified a mixture of multiple conformations coexisting for dimeric G-quadruplexes in solution. Here, we showed that the titration of BMPQ-1 shifted the conformational ensemble of multimeric G-quadruplexes towards (3+1) hybrid-2 topology, which became more pronounced as further G-quadruplex units are added.